PENDAMPINGAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) BAGI TENAGA KONSTRUKSI DI KOTA PALEMBANG - Heni Fitriani; Agus Lestari Yuono; Sakura Yulia Iryani; Citra Indriyati; Dinar Dwi Anugerah Putranto; Fajri Vidian (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
Work accidents in the construction industry are practically unavoidable, however they can be minimized. The aim of carrying out this community service is to socialize the importance of introducing occupational safety and health (K3) to protect and ensure the safety of every worker. Apart from that, it is also to increase safety and health awareness for workers in the construction projects and to increase awareness of the use of personal protective equipment for workers. Moreover, it is also to provide management recommendations for the layout of construction equipment and materials so as to create a safe working environment. The results showed that there was a significant increase between before the training and after training to the members for REI of South Sumatra. After the post-test was conducted in class, the community service activities was also integrated with lecture activities by inviting students to get involved in the construction projects.